An updated review of idiopathic osteosclerosis of the jaws - Ñahuincopa López, Paul Marcelo (2021)
Objective: The aim of this study was to update the concepts of the diagnosis of idiopathic osteosclerosis (IO) of the jaws by digital panoramic radiographs and cone beam tomography and describe the impact of this disease on oral and general health. Methods: A search of the main databases of dental medical research was carried out using the search terms “osteosclerosis, panoramic radiography, cone beam computed tomography, jaws”. Articles without language restriction until September 30, 2020, were identified. The prevalence and clinical and radiographic characteristics of IO of the jaws were examined in 2D and 3D imaging studies, as well as the interaction during treatments in the various dental specialties. Results: We analyzed the current situation regarding the diagnosis of IO, with an update of the diagnostic criteria used to accurately identify IO in the latest generation imaging studies, as well as determine its possible interactions in oral and general health. Conclusions: It is important to have a clear differential diagnosis of IO and be able to distinguish different radiopacities in the maxilla. Accurate reporting and monitoring of the morphometric characteristics are necessary taking into account the impact the presence of IO in the jaws has on future dental treatments.